Manner of being a historian: Cecilia Westphalen in the Brazilian historiography field of the second half of the twentieth century - Machado, Daiane Vaiz [UNESP] (Univ Federal Ouro Preto, Dept Historia, 2016)
This study investigates some facets of the intellectual route of CeciliaWestphalen (1927-2004). Our intention is to interpret her manner of being a historian in the tensions of Brazilian historiography of the second half of the twentieth century, time of outlining the craft contours as from the university institution. It was by the practice of economic and quantitative social history a la Annales, which she learned on the historiographical displacements to cole Pratique des Hautes Etudes, that Westphalen supported their research projects and guidelines for teaching. To understand them, stand out as fundamental the historicizing of her academic matches and mismatches configured in different places for sociability and production of knowledge, such as the Federal University of Paran, the Association of University Teachers of History and the Brazilian Society of Historical Research. To do so, we mobilize the intellectual production of Westphalen, her network of correspondence, academic meetings proceedings and minutes of departmental meetings.
Keywords: Intellectual history; Brazilian historiography; Cecilia Westphalen